Pedagogical Basis of Professional Training of Future Teachers - International Journal on Integrated Education (IJIE); Usarov Bobur Usarovich (International Journal on Orange Technologies, 2021)
This article discusses the pedagogical basis of professional training of future teachers and the content of their competency-based approach to their professional activities and provides methodological recommendations